Crowding Out of Long-Term Care Insurance: Evidence from European Expectations Data - Joan Costa-i-Font; Christophe Courbage (Center for Economic Studies and ifo Institute (CESifo), 2014)
Long-term care (LTC) is the largest insurable risk that old-age individuals face in most western societies. However, the demand for LTC insurance is still ostensibly small in comparison to the financial risk, which is reflected in the formation of expectations of insurance coverage. One explanation that has received limited support is that expectations of either public sector funding' and family bailout' crowd out individual incentives to seek insurance. This paper aims to investigate further the above mentioned motivational crowding out hypothesis by developing a theoretical model and by drawing on empirical analysis of representative survey data of fifteen European countries containing records on individual expectations of LTC funding sources (including private insurance, social insurance and the family). The theoretical model shows that, when informal care is treated as exogenously determined, expectations of both state support and informal care can potentially crowd out LTC insurance expectations, while this is not necessarily the case when informal care is endogenous to insurance, as is the case when intra-family moral hazard is integrated in the insurance decision. Evidence from expectations data suggest evidence consistent with the presence of family crowding out, but no evidence of public sector crowding out, and only weak evidence for cohorts of individuals older than 55.
Keywords: I18; D14; G22; 330; long-term care; old-age dependency; long-term care insurance; family crowding out; government crowding out